Electrochemical treatment of chicken slaughterhouse wastewater with iron electrodes - Thirugnanasambandham Karchiyappan; Parameswari Ettiyagounder; Paul Sebastian Selvaraj; Davamani Veeraswamy; Janaki Ponnusamy; Krishnan Ramanujam (Desalination and Water Treatment)
The electrochemical treatment (ECT) of synthetic chicken wastewater (SWW) and raw chicken industry wastewater (RCIW) was assessed at 15 V and 25 V, focusing on parameters such as pH, temperature, electrical conductivity (EC) removal, total dissolved solids (TDS) removal, chemical oxygen demand (COD) removal, electrical energy consumption (EEC), hydrogen (H2) production, sludge settling time, and electrode loss (EL). pH changes were voltage-dependent, with SWW shifting from highly acidic (2.7) to near-neutral (7.5) at 15 V and slightly alkaline (8.5) at 25 V, while RCIW showed minimal pH variation due to organic buffering. EC, TDS and COD removal was more efficient at 25 V for both SWW and RCIW. Sludge settling time was faster at 25 V compared to 15 V. H2 production and EL increased with voltage, with SWW producing 3.5 L/m³ of hydrogen at 25 V, compared to 2.4 L/m³ for RCIW. Operating cost of the ECT process in optimum conditions varies from 5 to 31 INR/m³ of RCIW. Fourier Transform Infrared (FTIR) spectroscopy, Thermogravimetric analysis (TGA), Raman spectra and Transmission Electron Microscopy (TEM) with Energy Dispersive X-ray Spectroscopy (TEM-EDX) are used to examine the sludge.